The COVID 19 pandemic from the primary care trenches - Claudia Bujold (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
The crisis facing primary care practices across America is real on multiple fronts. The COVID 19 pandemic is exposing broad weaknesses in our healthcare system; those of us who work in this space are in crisis mode wondering if we will be able to survive until the end of the year and beyond. To understand how we got here I must take you back a few years.